Analysis of Investment Interest in Chicken Farm in Kaligede Village, Senori District, Tuban Regency - Mohamad Ilham Putra Arifin; Rahman Amrullah Suwaidi (International Journal of Economics (IJEC), 2023)
In Kaligede Village, Senori District, Tuban, this study seeks to determine the impact of financial efficacy and financial literacy on investment interests. The sampling strategy employed in Method's research, which makes use of quantitative research techniques, is proportionate stratified random sampling. In this study, 95 households in Kaligede Village served as samples. As a consequence of this study, it has been determined that financial efficacy (X2) and financial literacy (X1) both significantly influence investing interest (Y). Using digital technology to read articles, watch videos, or use financial software to gain fundamental financial skills is advocated as a way for villagers to boost their financial literacy. In addition, villagers can also strengthen personal financial efficacy by building a support network, joining groups or communities that have similar interests related to finance.